Flavio-Shiró, sua pintura e sua plurisensorialidade - Piassi, Cláudia Stringari (2013)
Flavio-Shiro's familiar influence by oriental art is on of the requirements, among others, to understand the genesis of his shapes, lines, colors and gestures on painting work. Flavio-Shiro‟s dissertation, his painting and his diversity aims to study some